Development and application of an indirect ELISA for detecting equine IgG antibodies against Getah virus with recombinant E2 domain protein - Qiu, Xiangshu; Cao, Xinyu; Shi, Ning; Zhang, He; Zhu, Xiangyu; Gao, Yan; Mai, Zhanhai; Jin, Ningyi; Lu, Huijun (Frontiers in Microbiology, 2022)
Getah virus (GETV) disease is a mosquito-borne infectious disease that causes fever, aseptic meningitis, and abortion in a variety of animals. Currently, the epidemic trend of GETV disease increases seriously worldwide, especially in China, posing a potential threat to animal safety and public health. However, there are few reports about the epidemiological investigation of GETV disease in China as well as a lack of commercial diagnostic kit for GETV antibody. Therefore, the establishment of a rapid, sensitive and suitable GETV antibody detection method for large-scale samples is an urgent request to fully understand the prevalence of GETV disease. Here, a recombinant plasmid pET22b-GETV-E2d that contained the domain of GETV-E2 (E2d) protein fused to His-tag was constructed to express recombinant protein E2d (rE2d) in E. coli. The rE2d was mainly expressed in inclusion bodies. And it was purified successfully by nickel affinity column so that it could be used to develop an indirect ELISA (rE2d-ELISA). After optimizing reaction conditions of rE2d-ELISA, the cut-off value was determined as 0.396 with 100 equine sera tested by virus neutralization test (VNT). Furthermore, rE2d-ELISA method showed the positive rate of IgG antibodies against GETV was 54.3% based on testing 646 clinical serum samples obtained in Xinjiang whereas the overall coincidence rate between rE2d-ELISA and VNT was 94.0%, with 98.2% sensitivity and 92.6% specificity. The findings suggest that the developed IgG ELISA employing recombinant E2d promises was an efficient and low-cost type of antibody detection method for horse, which will benefit for prevention of GETV outbreaks in horses.